Stated beliefs and play in normal-form games - Miguel A. Costa-Gomes; Georg Weizsäcker (Osaka University, Institute of Social and Economic Research (ISER), 2004)
Using data on one-shot games, we investigate the assumption that players respond to underlying expectations about their opponent's behavior. In our laboratory experiments, subjects play a set of 14 two-person 3x3 games, and state first order beliefs about their opponent's behavior. The sets of responses in the two tasks are largely inconsistent. Rather, we find evidence that the subjects perceive the games differently when they (i) choose actions, and (ii) state beliefs - they appear to pay more attention to the opponent's incentives when they state beliefs than when they play the games. On average, they fail to best respond to their own stated beliefs in almost half of the games. The inconsistency is confirmed by estimates of a unified statistical model that jointly uses the actions and the belief statements. There, we can control for noise, and formulate a statistical test that rejects consistency. Effects of the belief elicitation procedure on subsequent actions are mostly insignificant.
Keywords: C72; C92; C51; D84; 330; noncooperative games; experimental economics; beliefs; bounded rationality; Erwartungstheorie; Verhalten; Nichtkooperatives Spiel; Normalformspiel